Single-particle tracking of the formation of a pseudoequilibrium state prior to charged microgel cluster formation at interfaces - Bi, Wuguo (2021)
The correlation between micron-sized particles and their self-assembly at fluid interfaces is important in several applications, including the stabilization of Pickering emulsions and creation of colloidosomes. In this study, through real-time visualization of the diffusion of microgel particles at the air–water interface of an aqueous pendant drop, the formation of a pseudoequilibrium state is observed prior to cluster formation. It is shown here that at the microscopic level, a pendant drop surface has nonuniform principal curvatures and exhibits positive deviatoric curvature (+∆c) gradients. The +∆c gradients confer superdiffusive motion to single ionic microgel particles and are responsible for bringing particles that are initially far apart to common sites on the interface with high curvatures. Prior to two-particle cluster formation, the balance between pairwise repulsion, capillary attraction and +∆c-induced energy that pushes the pair of particles to a high curvature creates a pseudoequilibrium state where the interparticle distance remains relatively invariant for a long period of time. This observation is also noted during higher-order cluster formation. Thereafter, a sufficiently strong long-range attraction potential is activated to facilitate cluster formation. Real-time tracking of the evolution of cluster formation provides useful insights into the interplay between various interactions experienced by ionic microgels.